Numerical modelling of the sedimentation and consolidation of tailings - Consoli, Nilo Cesar (1991)
The byproduct of processing rocks for the purpose of extraction of minerais is a waste which is generally referred to as tailings. These byproducts are impounded behind dams specially designed for thjs objective and are known as tailings deposits. The objective of this study is to investigate the true capacity of a reservoir when waste material is impounded. The process consists of dispersion, sedimentation and consolidation, which take place simultaneously. It is the purpose of the present study to analyze these coupled phenomena of soil formation to estimate the volume of waste that can be impounded. This is an important factor from a financiai and ecological view point. A theory is proposed which contains the sedimentation and consolidation processes. In arder to have a complete modelling of the problem an Implicit Finite Difference Code was developed. The code is based on the use of the Preissmann Scheme and the Double Sweep Method to solve the system of partial differential equations that form the sedimentation part of the problem. A new constitutive model for the characterization of the stress-strain behavior of the solid skeleton, considering the changes in the state of the material is developed. This forms an important part of the basic equation of the consolidation process coupling pore-pressure dissipation and deformation of the soil mass. A Finite Element Code is developed incorporating both nonlinearities, i.e. those arising from the material response (Elasto-Plastic Model) and those due to geometrical (Eulerian System) nonlinearities. To complement the study, the case of the disposal of a bauxite mine in a reservoir located in Saramenha, district of Ouro Preto, Minas Gerais, Brazil is considered. Comparison between numerical analysis and field measurements is made based on total and effective stresses profiles, void ratio profile and vertical displacements through the soil formation profile. The numerical analysis successfully predicts the filling of the reservoir, which helps build confidence in the numerical procedure developed in this study.